The influence of school climate towards counselor’s self-efficacy - Haron, Suzana; Wan Jaafar, Wan Marzuki; Baba, Maznah (Elsevier, 2010)
The purpose of this research is to specify whether there is any influence of school climate towards counselor’s self-efficacy. The subject of this research consists of 100 counsellors that were chosen randomly in secondary school in Malaysia. The instrument use for the research is based on questionnaire which is containing 3 sections. Section A contains of respondent background. Section B contains of “School Level Environment Questionnaire” (SLEQ). Section C contains of questionnaire regarding “School Counsellor Self-Efficacy Scale” (SCSE) and Section D contains of “Counselling Self-Estimate Inventory” (COSE). Pearson Product Moment Coefficient and Vicariate Linear Regression were used to analyze the data. The finding shows there is a significant relationship between school climate and counsellor’s self-efficacy. The Vicariate Linear Regression Analysis also showed that the school climate was a significant predictor towards counsellor’s self-efficacy. Pertaining to the research findings, several implications and recommendations were put forward.